Heirs' responsibility for the decedent's tax debts in the Republic of Slovenia - Podlipnik, Jernej (Array, 2019)
In this paper the author discusses the Slovenian tax rules on the responsibility of heirs for tax debts that their ancestors (decedents) had at death and also tax debts of the estate. Generally the heirs must fulfil all of them, but two groups of exceptions exist. The first one consists of exceptions applicable to all types of tax debts, e.g., liability only up to the amount of inherited property, liability of each heir in relation to his share of the inherited property, non-liability if the heir transfers the inheritance to the state or the local community, non-liability whenthe amount of tax is 80 EUR or lower. The second group of exceptions apply only to the personal income tax residents’ liability for that part of the personal income that is taxed annually (employment income, income from economic activity that is established on the basis of actual revenue and expenses, income from basic agricultural and basic forestry activities, income from transfer of property rights, and other income). Since personal circumstances (e.g. living costs, number of children, age) are taken into account when calculating the annual taxbase, the legislator believes that part of the personal income tax is a strictly personal obligation by nature. Hence, it ceases to exist when the tax debtor dies. The heirs are responsible for such tax debts only if the tax is either declared by the tax authority or by the deceased when he is still alive. The author of this paper claims that because the responsibility of the heirs depends on the activity of the tax authority or on the deceased taxpayer and not only on the moment of death, the constitutional equality before the law clause is breached.